Chronic non-bacterial osteomyelitis with autoimmune hepatitis a case report and literature review - Jin, M (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2023)
Objective: To summarize the clinical characteristics and treatments of chronic non-bacterial osteomyelitis with autoimmune hepatitis in children. Methods: A child who had chronic non-bacterial osteomyelitis with autoimmune hepatitis was admitted to the Department of Gastroenterology of the Children's Hospital Capital Institute of Pediatrics at April 2022. The clinical data was retrospectively analyzed. Using the keywords of "chronic non-bacterial osteomyelitis""autoimmune hepatitis" in Chinese and English, the literature from database establishment to December 2022 in CNKI, Wanfang, China Biomedical Literature Database and Pubmed was searched. Combined with this case, the clinical characteristics and treatment of chronic non-bacterial osteomyelitis combined with autoimmune hepatitis were analyzed. Results: A 5 years and 3 months girl was admitted to the Department of Gastroenterology of Children's Hospital, Capital Institute of Pediatrics for "transaminase elevated for 1 year and swelling of right maxillofacial area for half a year". The physical examinations at admission found a 4.0 cm × 4.0 cm swelling area with tenderness before the right ear, abdominal distention with visible abdominal wall vein, firm and enlarged liver (10.0 cm below the xiphoid and 4.5 cm below the right ribs), and splenomegaly (Line Ⅰ 10.0 cm, Line Ⅱ 11.5 cm, and Line Ⅲ 25.0 cm). There was no redness, swelling or restriction of the limbs. Laboratory examination found abnormal liver function with alanine aminotransferase 118 U/L, aspartate aminotransferase 227 U/L, γ-glutamyltransferase 360 U/L, and positive direct anti-human globulin test; immunology test found immunoglobulin G 41.60 g/L and a homogeneous type of antinuclear antibody of 1∶1 000; the autoimmune hepatitis antibody test found a positive anti-smooth muscle antibody (1∶100). Liver biopsy showed moderate interfacial inflammation and the patient was diagnosed with autoimmune hepatitis (International Autoimmune Hepatitis Group 19). The imaging findings showed extensive involvement of the bilateral mandible, while the right side was severe. There were expansile bone changes, thinning of the bone cortex, and significant swelling of the surrounding soft tissue in the mandibular body, mandibular angle, and mandibular ramus. After treatment of glucocorticoid, the swelling of the right maxillofacial region disappeared and the transaminase returned to normal. Only one case was reported before in English and none in Chinese. The two cases were both girls whose main clinical features were joint pain and swelling. The previous case started with pain in both knee joints, and developed liver injury during treatment while this case had liver injury as the initial clinical presentation. Besides, the affected sites and degrees of arthritis in the 2 cases were different. After glucocorticoid treatment, the clinical symptoms were alleviated, and transaminases returned to normal. Conclusions: Chronic non bacterial osteomyelitis may involve the liver and manifest as autoimmune hepatitis. Glucocorticoids therapy is effective